Heavy Metal Detection in Medicinal Herbs Using Laser-Induced Breakdown Spectroscopy - Chew, Lee Chie; Syed Zuhaib Haider Rizvi (Enhanced Knowledge in Sciences and Technology, 2022)
Medicinal plants are the source of medication that has been widely used in Malaysia. The environmental pollution due to the development and revolution of industries worldwide will cause medicinal herbs to be contaminated with toxic metals. A healthy human body required essential elements to maintain functional roles such as diverse physiological and biochemical activities in the body. Laser-induced breakdown spectroscopy (LIBS) is a powerful elemental analysis technique. The single pulse, ungated LIBS system using Nd: YAG laser of 1064 nm and HR4000 spectrometer is used in this investigation to analyze the mineral composition in medicinal herbs spectroscopically. The herbs in the research are Menthapiperita L and Aloe Barbadensis miller. Although these herbs are commercially utilized, the overuse of pesticides and herbicides causes heavy metals pollution in soil and gradually accumulates in plants. The observed spectral lines obtained from the herbs in the LIBS spectra are used to identify the heavy metal elements. The laser-induced breakdown (LIB) spectra elucidate the presence of essential elements of metal like Al, C, Ca, Cu, Fe, K, Mg, Na, Si, and Zn in medicines. The results obtained have detected the presence of toxic heavy metals such as Cd,  Pb, Co, and Ni on the overuse of pesticides, insecticides, herbicides, and fertilizers. LIBS can be a very helpful tool in analyzing the chemical composition of medicinal plants that can be used for quality control and monitoring purposes. Dispersive X-Ray Analysis (EDX) is performed to validate the presence of heavy metals identified in LIBS spectra of the samples.